CMLs Macro Leap 20 Micro-Credentials for 2024 - Nor Yazi, Khamis; Amy Zulaikha, Mohd Ali; Noraisah Nurul Fatwa, Mohd Razali (UMPSA, 2025)
The Centre for Modern Languages (CML) at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has distinguished itself with 20 Micro-Credentials, marking a significant milestone achieved in 2024 that commenced in 2021.